Analisis Strategi Pemasaran dalam Upaya Meningkatkan Penjualan Produk Kerajinan Tembaga dan Kuningan CV. Logam Jaya Gallery di Desa Tumang - Aulia Ayu Damayanti; Naswa Mar’atus Sholihah; Shella Wulandari; Mellyana Herawati; Muhammad Aditya Yuliyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This in-depth study explores the comprehensive marketing strategies implemented by CV. Logam Jaya Gallery, a leading copper and brass craft business entity in Tumang Village, Boyolali. The research aims to identify the key factors behind the company's resilience in the face of intense industry competition. Using a qualitative approach, operational data was obtained in depth. The results show that the company integrates direct marketing through national and international exhibitions, while optimizing digital channels and e-commerce for broader global market penetration. Despite its success, CV. Logam Jaya Gallery faces significant obstacles such as market demand fluctuations, limitations in manual production technology, and competitive pressures. As a mitigation measure, the company diversifies its products and adopts contemporary technology to efficiently increase its operational capacity. Strategic synergies with the government and the private sector were also strengthened to expand promotional access. This success was also supported by fundamental pillars in the form of cultural heritage and intergenerational craftsmanship. Through a combination of organized management, sustainable design innovation, and adaptation to market dynamics, the company has succeeded in establishing itself as a competitive creative industry player on the national and global stage.